Covid-19 and the Information Crisis of Liberal Democracies: Insights from Anti-Disinformation Action in Italy and EU - Fabrizio Di Mascio (Coordinamento SIBA, 2021)
Action against disinformation has become more important than ever in the context of the Covid-19 pandemic. This is due to the synchronous global scale of the problem and its potentially deadlier consequences as the public seeks out guidance regarding what they might do to lower the risk of infection. This article investigates the impact of the Covid-19 crisis on the regulation of social media platforms as it is mediated by the legacy of previous responses to disinformation. It shows that the Covid-19 crisis has catalyzed the shift to co-regulatory approaches that imposed reporting obligations on platforms at the European level. It also raises concerns about the implementation of the new European regulatory package that will largely depend on the initiatives of individual Member States such as Italy, where the low level of societal resilience to disinformation increases the incentives for political leaders to ignore the problem of disinformation.